Efficacy of Terminalia catappa leaves extract as an antimicrobial agent against pathogenic bacteria - Muhammad Iskandar Abdullah,; Mohd Fakharul Zaman Raja Yahya,; Latifah Munirah Bakar,; Nurul Aili Zakaria,; Darah Ibrahim,; Mohd Taufiq Mat Jalil, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Terminalia catappa (“Ketapang” in Malay) is a plant that belongs to the family Combreteceae and is native to Southeast Asia. Various parts of this plant were reported to possess bioactive compounds with antimicrobial properties. However, reports on the antimicrobial activity of different ages of T. catappa leaf (TCL) against pathogenic bacteria are lacking. This study investigated the antibacterial activity of the different ages of TCL extracts against the pathogenic bacteria, Staphylococcus aureus and Escherichia coli. Disk diffusion assay was carried out to determine the antibacterial activity of different ages of TCL extracts. Meanwhile, the efficacy of the different leaf extracts was evaluated by performing broth microdilution (MIC & MBC determination), growth reduction, time-kill study, and membrane cell leakage assay (MCLA). The findings revealed that the extracts showed greater antibacterial activity toward the Gram-positive S. aureus compared to Gram-negative E. coli, with diameter of inhibition zone ranging from 12.33±0.53 mm to 26.33±1.4 mm and 9.23±0.32 mm to 16.21±0.42 mm, respectively. The mature leaf extract (MLE) and senescent leaf extract (SLE) exhibited higher antibacterial activity compared to young leaf extract (YLE) and shoot leaf extract (ShLE) for both Gram-positive and Gram-negative bacteria. The broth microdilution assay showed all the different ages of TCL extracts exhibited bactericidal effects towards S. aureus. Meanwhile, the YLE and ShLE showed a bacteriostatic effect on E. coli, whereas the MLE and SLE exerted bactericidal action. The time-kill study revealed that the extract activity was time- and concentration-dependent. The results of the MCLA corroborated the time-kill study, which showed that a higher concentration of extract could successfully inhibit and kill the bacterial cells, as indicated by higher protein and nucleic acid leakage. The present study suggests that all different ages of TCL extracts, particularly the MLE can act as potential antibacterial agents against both Gram-positive and Gram-negative bacteria.